Women as Terrorists: a Motivational Factor Becomes a Terrorist In Indonesia - Ningsih Wirandari; Zuli Qodir (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
This study aims to determine whether women's motivation to become terrorists can threaten state security in Indonesia. This article shows that women are actors who play an active role in several acts of terrorism in the country. Factors that cause this to become a terrorist are low family, political and social economics, cultural influences, and ideology of religious beliefs. Terrorist acts carried out by women involve suicide bombings, destruction of public facilities, and destruction of houses of worship in several areas affected by terrorist acts. Researchers conducted research by analyzing data obtained from social media sources for data collection. After the data was received, it was processed through NVivo 12 Plus to make it more interesting. The theory used in this study uses the ladder of terrorism theory. The limitation of this research is that it uses only a few social media as data sources, so further research is expected to add richer data to expand the study.